CORPORATE GOVERNANCE IMPLEMENTATION AND PERFORMANCE ASSESMENT USING THE CGCGâs UGM RATING MODEL: COMMERCIAL BANKS IN INDONESIA - Artiningsih, Arika; Novmawan, M. Ridwan; Warsono, Sony (Journal of Indonesian Economy and Business, 2011)
The purpose of this research is to examine the implementation of Good CorporateÂ Governance (GCG) in Commercial Banks before and after the policy of The Bank IndonesiaÂ Regulation (PBI) Number 8/4/PBI/2006 concerning Good Corporate GovernanceÂ Implementation for Commercial Banks. Center for Good Corporate Governance UniversitasÂ Gadjah Mada (CG CGCG UGM) rating model was employed to measure CG implementationÂ in Commercial Banks which calculate both company organs and Corporate Governance (CG)Â basic principles in a universal framework. From the company organs perspective, a CGÂ system consists of five (5) organs interacting each others, which are board of directors, boardÂ of executives, boards of commissioners/committees, auditors, and stakeholders. Meanwhile,Â from the CG basic principles perspective, a CG system should fulfill five (5) CG principles,Â which are Transparency, Accountability & Responsibility, Responsiveness, Independency, andÂ Fairness. Therefore, the CG framework and rating model use The information technology asÂ the main pillar in the application of CG. As for measuring banking performance, CAMELÂ ratio–which consist of the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Management (Man), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR)–wasÂ applied. In conclusion, Using CGCG UGM rating model, it is discovered hat CGimplementation at Indonesian banking system was improved subsequently to the issuance ofÂ PBI. Whereas on its performance, the significant changes were indicated by only two ratios,Â i.e. LDR and MAN. This research depicts Bank Indonesia effectiveness as regulator atÂ providing CG implementation guide on PBI. This research reveals for the urge for IndonesianÂ banking industry to boost GCG implementation for their rating and performanceimprovement.Â Keywords: corporate governance asessment, CAMEL, commercial banks, corporateÂ governance